PESERTA DIDIK KELAS VIII SMP NEGERI 11 JAYAPURA PADA POKOK BAHASAN GETARAN DAN GELOMBANG - Nofriana Tajo; Auldry F. Walukow Fransje Walukow; Florentina Maria Panda (Papua Journal of Physics Education, 2020)
The aim of this research was to determine the increase, the relationship, and the influence of learning using (Problem Based Learning) PBL models based on experimental method on student learning outcomes. This research was carried out using quantitative approach with experimental research methods. Pre-experimental design was done using one-group pretest-posttest design. The study was conducted in SMP Negeri 11 Jayapura in academic year 2018/1019. The population were 227 students of class VIII. The research samples were VIII G consisted of 30 students. The analysis technique used is N-Gain analysis. Based on research results, it is obtained that there is an increase in learning outcomes indicated by the obtained score which was 0.76. It was included in the high category. Asymp Value. Sig. (2-tailed) = 0,000 <0.05, then Ho is rejected and Ha is accepted, meaning that there is a relationship between PBL models based on experimental method on student learning outcomes. Pearson Correlation value = 0.769 is interpreted to have a strong relationship. The value of R Square = 0.591 means that the influence of the PBL model based on the experimental method on learning outcomes was 59.1%. The sig. value = 0.00 <0.05, then Ho is rejected and Ha is accepted, meaning that there is an influence of PBL model based on experimental method on learning outcomes.Keywords: PBL model, experimental method, learning outcomes.